Mobile Learning Applications for Islamic Studies: A Systematic Review of Design Principles and Learning Outcomes - Ibadurrahman, Muhammad; Asep Supriyadi; Muhamad Nizan Solahudin; Wawan Ridwan; Lina Nuraini; Aas Solihat; Andriyana Andriyana (PT. Banjarese Pacific Indonesia, 2025)
The advancement of digital technology has paved the way for the emergence of various mobile learning applications increasingly used within the context of Islamic education. This phenomenon not only reflects the trend of integrating technology into modern learning systems but also raises fundamental questions about how these applications are designed and how far they impact learners’ experiences and learning outcomes. This article presents a systematic review of scholarly studies discussing the use of mobile applications in Islamic studies education. The review focuses on two key aspects: the design principles employed in application development and the learning outcomes achieved following their use. The review involved selecting literature from the past six years using specific inclusion criteria, including content relevance, source credibility, and its connection to mobile learning practices in Islamic education. Analysis reveals that designs considering cultural appropriateness, user interface interactivity, and integration of Islamic values positively influence students' emotional engagement, motivation, and content comprehension. Learning outcomes also extend into affective and spiritual domains, not merely cognitive. These findings serve as an initial foundation for developers and educators to build an adaptive, meaningful, and value-based Islamic mobile learning ecosystem.